Attenuation of High-Fat Diet-Induced Rat Liver Oxidative Stress and Steatosis by Combined Hydroxytyrosol- (HT-) Eicosapentaenoic Acid Supplementation Mainly Relies on HT. (2nd July 2018) - Echeverría, Francisca; Valenzuela, Rodrigo; Bustamante, Andrés; Álvarez, Daniela; Ortiz, Macarena; Soto-Alarcon, Sandra A.; Muñoz, Patricio; Corbari, Alicia; Videla, Luis A.
Abstract : Pharmacological therapy for nonalcoholic fatty liver disease (NAFLD) is not approved at the present time. For this purpose, the effect of combined eicosapentaenoic acid (EPA; 50 mg/kg/day) modulating hepatic lipid metabolism and hydroxytyrosol (HT; 5 mg/kg/day) exerting antioxidant actions was evaluated on hepatic steatosis and oxidative stress induced by a high-fat diet (HFD; 60% fat, 20% protein, and 20% carbohydrates) compared to a control diet (CD; 10% fat, 20% protein, and 70% carbohydrates) in mice fed for 12 weeks. HFD-induced liver steatosis (i) was reduced by 32% by EPA, without changes in oxidative stress-related parameters and mild recovery of Nrf2 functioning affording antioxidation and (ii) was decreased by 42% by HT, concomitantly with total regain of the glutathione status diminished by HFD, 42% to 59% recovery of lipid peroxidation and protein oxidation enhanced by HFD, and regain of Nrf2 functioning, whereas (iii) combined EPA + HT supplementation elicited 74% reduction in liver steatosis, with total recovery of the antioxidant potential in a similar manner than HT. It is concluded that combined HT + EPA drastically decreases NAFLD development, an effect that shows additivity in HT and EPA effects that mainly relies on HT, strengthening the impact of oxidative stress as a central mechanism underlying liver steatosis in obesity.